2017
DOI: 10.1585/pfr.12.1401010
|View full text |Cite
|
Sign up to set email alerts
|

An Explosive Scaling Law for Nonlinear Magnetic Reconnection and Its Insensitivity to Microscopic Scales

Abstract: The nonlinear phase of magnetic reconnection is investigated by numerically solving a gyrofluid model. The scaling law for the explosive reconnection rate, which has been recently derived for an ideal two-fluid model [Hirota et al., Phys. Plasmas 22, 052114 (2015)], is found to consistently hold when either the ion-sound gyroradius ρ S or the ion gyroradius ρ i is comparable to the electron skin depth d e , even in the presence of finite resistivity η. In this explosive phase, a local X-shaped current layer is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Hirota reported the progress on a theory for explosive reconnection based on the gyrofluid energy principle framework 29 . Two-fluid model including the Larmor radius effect is applied, in which the governing equations are the continuty and momentum equations for ions and electrons.…”
Section: Reconnection and Particle Accelerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hirota reported the progress on a theory for explosive reconnection based on the gyrofluid energy principle framework 29 . Two-fluid model including the Larmor radius effect is applied, in which the governing equations are the continuty and momentum equations for ions and electrons.…”
Section: Reconnection and Particle Accelerationmentioning
confidence: 99%
“…The plasmoid instability is shown in right panels. Reprinted from[29], with permission from JSPF. the energy principle based on gyro-fluid is applied to the tearing instability, it is found that:(i) only a two-parameter trial function for the inner layer ( i.e.…”
mentioning
confidence: 99%